Effectiveness of Diets Incorporating Nano-Zeolite and Urea-Impregnated Nano-Zeolite on Fermentation Efficiency in Rumen Fluid In Vitro - Dede Kardaya; Pia Nurmala Dewi; Deden Sudrajat; Dewi Wahyuni; Ikhsan Qodri Pramartaa; Ruslan Abdul Gopar; Windu Negara; Raden Siti Nurlaela (Universitas Djuanda, 2025)
Zeolite had been widely investigated in animal feed for its ability to improve feed efficiency and reduce ammonia emissions, and nano-zeolite offered greater adsorption capacity due to its expanded surface area. This study evaluated the effects of nano-zeolite supplementation on ammonia (NH₃), volatile fatty acids (VFA), the VFA/NH₃ ratio, and pH during in vitro rumen fermentation. A two-factor randomized block design (6 × 6) with four replicates was used. Incubation time (2, 4, 8, 12, 24, and 48 h) served as the first factor, and six dietary treatments served as the second factor: control, urea-supplemented concentrate, inactivated nano-zeolite, activated nano-zeolite, urea-impregnated inactivated nano-zeolite, and urea-impregnated activated nano-zeolite. Nano-zeolite, whether active or urea-impregnated, did not significantly improve rumen fermentation efficiency based on NH₃, VFA, or VFA/NH₃ ratio. All nano-zeolite diets performed similarly to the control and urea-only diets. Fermentation efficiency peaked at 4 and 8 hours of incubation, indicating that nano-zeolite combined with urea supported stable fermentation, particularly during early to mid-incubation.